Assessment of Japanese iodine intake based on seaweed consumption in Japan: A literature-based analysis - Zava, Theodore T (BioMed Central, 2011)
Japanese iodine intake from edible seaweeds is amongst the highest in the world. Predicting the type and amount of seaweed the Japanese consume is difficult due to day-to-day meal variation and dietary differences between generations and regions. In addition, iodine content varies considerably between seaweed species, with cooking and/or processing having an influence on iodine content. Due to all these factors, researchers frequently overestimate, or underestimate, Japanese iodine intake from seaweeds, which results in misleading and potentially dangerous diet and supplementation recommendations for people aiming to achieve the same health benefits seen by the Japanese. By combining information from dietary records, food surveys, urine iodine analysis (both spot and 24-hour samples) and seaweed iodine content, we estimate that the Japanese iodine intake--largely from seaweeds--averages 1,000-3,000 μg/day (1-3 mg/day).